Mechanisms of Inflammation in Neutrophil-Mediated Skin Diseases - Marzano, Angelo V.; Ortega-Loayza, Alex G.; Heath, Michael; Morse, Daniel; Genovese, Giovanni; Cugno, Massimo (Frontiers in Immunology, 2019)
Neutrophil-mediated skin diseases, originally named neutrophilic dermatoses, are a group of conditions due to an altered neutrophil recruitment and activation, characterized by polymorphic cutaneous manifestations with possible internal organ involvement. Although a number of diseases are included in this setting, the two prototypic forms are pyoderma gangrenosum and Sweet’s syndrome which usually present with skin ulcers and plaque-type lesions, respectively. They have central features significantly overlapping with autoinflammatory conditions which manifest as repeated episodes of tissue inflammation. However, in contrast to appropriate inflammatory responses to insults or to autoimmune disease, there is an absence of identifiable pathogens, autoantibodies, or autoreactive lymphocytes. The recognition of monogenic autoinflammatory diseases which can present with neutrophilic dermatoses has led to study several genes involved in autoinflammation in neutrophilic dermatoses. Based on discovering of a number of mutations involving different autoinflammatory genes, neutrophil-mediated skin diseases are nowadays regarded as a spectrum of polygenic autoinflammatory conditions. Although disease mechanisms have not yet been completely elucidated, neutrophilic dermatoses are recognized as diseases involving dysfunctional cellular signalling mediated by pathways mainly related to inflammasome and IL-1 with the contributory role of IL-17 and other effector molecules. The precise elucidation of the above mentioned pathologic mechanisms may pave the way to tailored treatments for patients with different neutrophil-mediated skin diseases.